2004
DOI: 10.1128/mcb.24.10.4083-4091.2004
|View full text |Cite
|
Sign up to set email alerts
|

Key Role of Ser562/661 in Snf1-Dependent Regulation of Cat8p in Saccharomyces cerevisiae and Kluyveromyces lactis

Abstract: Utilization of nonfermentable carbon sources by Kluyveromyces lactis and Saccharomyces cerevisiae requires the Snf1p kinase and the Cat8p transcriptional activator, which binds to carbon source-responsive elements of target genes. We demonstrate that KlSnf1p and KlCat8p from K. lactis interact in a two-hybrid system and that the interaction is stronger with a kinase-dead mutant form of KlSnf1p. Of two putative phosphorylation sites in the KlCat8p sequence, serine 661 was identified as a key residue governing K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…Unphosphorylated Cat8 appears to be competent to bind because Heisinger et al (69) found that bacterially produced Cat8, which is not expected to receive its normal modifications, showed in vitro DNA binding. Phosphorylation is important to the activator function of Cat8 because a S562E point mutation in Cat8, which mimics the phosphorylated state, shows some constitutive activity (15). In support, the genes that we find to be the least Cat8-dependent, ICL2 and POT1, have the highest expression in repressed REG1⌬hda1⌬rpd3 cells (Fig.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Unphosphorylated Cat8 appears to be competent to bind because Heisinger et al (69) found that bacterially produced Cat8, which is not expected to receive its normal modifications, showed in vitro DNA binding. Phosphorylation is important to the activator function of Cat8 because a S562E point mutation in Cat8, which mimics the phosphorylated state, shows some constitutive activity (15). In support, the genes that we find to be the least Cat8-dependent, ICL2 and POT1, have the highest expression in repressed REG1⌬hda1⌬rpd3 cells (Fig.…”
supporting
confidence: 65%
“…In HDAC mutants, the Adr1 and Cat8 activators, which normally bind to glucose-repressed promoters only in low glucose conditions, bound constitutively. SNF1, which encodes the yeast AMP kinase homolog that is regulated by environmental stresses, was required for the constitutive activator binding as it is for binding in glucosederepressing conditions (13)(14)(15). At the Adr1-and Cat8-regulated ADH2 promoter, a complex was assembled that contained Pol II and components of SAGA, SWI/SNF, TFIIB, and Mediator.…”
mentioning
confidence: 99%
“…Cat8 activity is regulated on two levels: its expression is Mig1 repressed (145,257), and its capacity to activate transcription requires a functional Snf1 kinase (303). Snf1 phosphorylates Cat8 in ethanol-grown cells (56,303); following the addition of glucose, it is dephosphorylated in a Glc7-independent manner (303). Interestingly, constitutively expressed Cat8 fused to the Ino2 activation domain bypasses the need for a functional Snf1 in cells growing on ethanol (300).…”
Section: Snf1-mediated Signal Transduction In Glucose Repression and mentioning
confidence: 99%
“…This widely acting transcriptional repressor exits the nucleus when phosphorylated, relieving repression of dozens of genes, including CAT8 (13). Subsequent production of the Cat8 transcription factor and activation via Snf1-dependent phosphorylation (11,36) up-regulates gluconeogenic and glyoxylate cycle genes as well as several transcription factors, such as SIP4 and HAP4 (6,25).…”
mentioning
confidence: 99%